2013
DOI: 10.1111/acem.12168
|View full text |Cite
|
Sign up to set email alerts
|

Rising Annual Costs of Dizziness Presentations to U.S. Emergency Departments

Abstract: Objectives: Dizziness and vertigo account for roughly 4% of chief symptoms in the emergency department (ED). Little is known about the aggregate costs of ED evaluations for these patients. The authors sought to estimate the annual national costs associated with ED visits for dizziness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
232
5
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(246 citation statements)
references
References 23 publications
4
232
5
5
Order By: Relevance
“…§Most of the patients were examined within 24 hours of symptom onset and almost all within 72 hours. ‖In the 14 with early false-negative MRI (<48 hours), follow-up ("final") MRI-DWI an average of about 3 days after symptom onset (range = 2-10 days) revealed infarctions located in the lateral medulla (11, one extending to the pons and one associated with a cerebellar infarction), middle cerebellar peduncle (2), and pontomesencephalic junction (1). Two of these false-negative initial MRI patients deteriorated substantially and one died.…”
Section: Discussionmentioning
confidence: 99%
“…§Most of the patients were examined within 24 hours of symptom onset and almost all within 72 hours. ‖In the 14 with early false-negative MRI (<48 hours), follow-up ("final") MRI-DWI an average of about 3 days after symptom onset (range = 2-10 days) revealed infarctions located in the lateral medulla (11, one extending to the pons and one associated with a cerebellar infarction), middle cerebellar peduncle (2), and pontomesencephalic junction (1). Two of these false-negative initial MRI patients deteriorated substantially and one died.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that increasing number of patients reporting dizziness has been admitted to hospital. At the same time, the frequency of doing the imaging tests has also increased (Saber Tehrani et al 2013).…”
Section: Epidemiologymentioning
confidence: 99%
“…Despite extensive emergency department (ED) workups, the diagnostic accuracy of a central cause of AVS is low (approximately 35% of strokes are missed). 3,4 If patients who present with AVS have focal neurologic signs, stroke will be diagnosed relatively easily. However, only around 20% do present with focal signs, and the remainder have isolated AVS.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, although the prevalence of stroke in isolated AVS is low (approximately 1%), 9 neuroimaging is overused to exclude stroke because of an absence of rules for determining appropriate use. 3 For instance, an international survey of emergency physicians found that the top adult emergency medicine priority for clinical decision procedures was a rule for when to image patients with vertigo. 10 The aim of the present study was to investigate predictive factors of stroke that can easily be used by a range of clinical staff in patients with isolated AVS.…”
Section: Introductionmentioning
confidence: 99%